UPAYA SEKOLAH DALAM MEMBINA AKHLAK PESERTA DIDIK DI SMP MUHAMMADIYAH 7 PROGRAM UNGGULAN COLOMADU - Kusuma, Azzahra Dian; Azani, Mohammad Zakki (PAI RAFAH, 2024)
The principal is a leader in an institution, namely a school, who has full responsibility for the school he leads. One of these responsibilities is to ensure that every student does righteous deeds, in accordance with Islamic values. This study aims to look at the principal's efforts to cultivate morals at SMP Muhammadiyah 7 Colomadu Superior Program, in this case, the teacher is always a good example for students so that students are inspired by the akhlakul kharimah that is exemplified. The method used in this research is through data collection techniques and interviews, which are conducted using a phenomenological qualitative approach. The object of this research is the principal, teachers, and students at the junior high school. The sources used are data from data collection and interviews. The results of this study can be seen that the principal's efforts to foster the morals of students are by creating programs, such as internship programs, specialization classes, joint dhuha prayers, murotal activities together before learning activities, and before asr prayers, Sunday morning congregation activities every two months, and tahfidz quarantine., besides that, it also provides good examples related to morals to students and gives advice to students related to morals.